Upaya meningkatkan hasil belajar matematika siswa Kelas III MINU Tratee Putera Gresik pada materi perkalian melalui pendidikan matematika realistik - Alviani, Fauziah Ninik (Maliki Interdisciplinary Journal, 2025)
The aim of this research is to use the Realistic Mathematics Education (RME) technique to improve the mathematics multiplication learning outcomes of class III MINU Trate Putera Gresik students. The problem is the low daily test scores of students who do not meet the Minimum Completeness Criteria (KKM) of 75 points. There are two cycles to this research project. In cycle I, planning includes creating physical learning media, worksheets and observations, while implementation includes group discussions and evaluation. The results showed an increase in the number of students who met the criteria from 16 to 19, with the average score increasing from 68 to 80. In cycle II, the plan was updated based on cycle I reflections, emphasizing practical mathematics and group discussions using real objects. After implementation and assessment, the class average score increased to 87. The successful completion of cycle II is proof that this research’s realistic mathematics learning method can improve students’ understanding and performance.